Barriers to Performing Stretching Exercises Among Korean‐Chinese Female Migrant Workers in Korea. Issue 2 (22nd January 2014) - Lee, Hyeonkyeong; Wilbur, JoEllen; Chae, Duckhee; Lee, Kyongeun; Lee, Meenhye
Abstract: Objective: The purpose of this study was to investigate the barriers to performing stretching exercise experienced by Korean‐Chinese female migrant workers during a community‐based 12‐week stretching exercise intervention trial. Design and Sample: Qualitative secondary data analysis was conducted using telephone counseling interview transcripts from 27 middle‐aged, Korean‐Chinese migrant women workers. Measures: A semistructured interview question asking barriers to performing stretching exercise was given to women who did not adhere to recommended stretching exercise. During the 12‐week home‐based stretching exercise intervention trial, six telephone calls were made to participants biweekly to elicit barriers to performing stretching exercise. Directed content analysis approach was utilized using three barrier categories: intrapersonal, interpersonal, and work‐related environmental factors based on the ecological model. Results: Participants experienced an average of 2.5 barriers during the study period. Intrapersonal barriers included lack of time and lack of motivation, and interpersonal barriers included no family to provide support and also a feeling resistance from coworkers. Work‐related environmental barriers included frequent job changes, long working hours, lack of rest time, and unpredictable job demands. Conclusions: The findings highlight that migrant workers in Korea face unique work‐related difficulties which present barriers to exercise.